Assistance in the Preparation of PjBL LKPD for Deepening Science for Grade V Elementary School - Candra Utama; Aynin Mashfufah (Abdi Masyarakat, 2026)
This community service article describes mentoring for developing Project Based Learning (PjBL)-oriented student worksheets to strengthen grade V elementary science learning. The program was implemented at SDN Kalisongo 1 Kota Malang with teachers as the target group. The mentoring combined adult learning, brainstorming, conceptual reinforcement on PjBL, guided worksheet design, presentation, reflection, and pretest-posttest evaluation. The results indicate an increase in teacher understanding from a pretest mean of 48.58 to a posttest mean of 68.88. Normality and homogeneity assumptions were met, and the paired t-test showed a significant difference between pretest and posttest scores, t(23) = -30.337, p < 0.001. The mentoring supported teachers in translating classroom problems into project triggers and in preparing PjBL-based worksheets for science learning. Follow-up support is recommended to test the worksheets directly in classroom practice and to integrate digital or artificial intelligence-based tools into the next mentoring cycle.